Understanding the factors influencing fall armyworm (Spodoptera frugiperda J.E. Smith) damage in African smallholder maize fields and quantifying its impact on yield: a case study in eastern Zimbabwe - Baudron, Frédéric; Zaman-Allah, M.A.; Chaipa, I.; Chari, N.; Chinwada, P. (Elsevier, 2019)
Fall armyworm (FAW, Spodoptera frugiperda J.E. Smith) is an invasive lepidopteran pest established in most of sub-Saharan Africa since 2016. Although the immediate reaction of governments has been to invest in chemical pesticides, control methods based on agronomic management would be more affordable to resource-constrained smallholders and minimize risks for health and the environment. However, little is known about the most effective agronomic practices that could control FAW under typical African smallholder conditions. In addition, the impact of FAW damage on yield in Africa has been reported as very large, but these estimates are mainly based on farmers' perceptions, and not on rigorous field scouting methods. Thus, the objectives of this study were to understand the factors influencing FAW damage in African smallholder maize fields and quantify its impact on yield, using two districts of Eastern Zimbabwe as cases. A total of 791 smallholder maize plots were scouted for FAW damage and the head of the corresponding farming household interviewed. Grain yield was later determined in about 20% of these fields. FAW damage was found to be significantly reduced by frequent weeding operations and by minimum- and zero-tillage. Conversely, pumpkin intercropping was found to significantly increase FAW damage. FAW damage was also found to be higher for some maize varieties, although these varieties may not be the lowest yielding. If the incidence of plants with FAW damage symptoms recorded in this research (32–48%, depending on the estimate used) is commensurate with what other studies conducted on the continent found, our best estimate of the impact of FAW damage on yield (11.57%) is much lower than what these studies reported. Although our study presents limitations, losses due to FAW damage in Africa could have been over-estimated. The threat that FAW represents for African smallholders, although very real, should not divert attention away from other pressing challenges they face.